Penerapan Zahir Accounting Untuk Pengelolaan Data Akutansi Pada CV. Kevindo Auto - Muhamad Nasihin (LPPM Universitas Bina Sarana Informatika, 2021)
CV. Kevindo Auto is a company engaged in the automotive sale and purchase of used cars. Accounting data processing system at CV. Kevindo Auto is still done by manual recording. This can lead to high risks that may occur with this manual recording system, including frequent errors in recording transactions, difficulty finding transaction evidence and losing proof of transactions that occur at the company. CV. Kevindo Auto requires a computerized system that will be able to provide convenience in recording all transactions that occur up to the reporting process. The use of the zahir accounting program is the right solution for solving problems that occur in this company. Using the zahir accounting program can shorten the time and simplify the process of managing accounting data. Accounting data stored on a computer makes filing safer and easier and faster in the reporting process.